NIH stroke scale and unfavourable outcomes in acute ischaemic stroke: retrospective study - Tramonte, Maiara Silva [UNESP]; Carvalho, Ana Claudia Pires [UNESP]; Fornazari, Ana Elisa Vayego [UNESP]; Boas, Gustavo Di Lorenzo Villas [UNESP]; Modolo, Gabriel Pinheiro [UNESP]; Ferreira, Natalia Cristina [UNESP]; Lange, Marcos Christiano; Minicucci, Marcos Ferreira [UNESP]; Bazan, Rodrigo [UNESP]; Gomes Lopes, Laura Cardia [UNESP] (Bmj Publishing Group, 2022)
Objectives To evaluate the determining factors of severe functional impairment (SFI) outcome at discharge and in-hospital mortality in patients who had an acute ischaemic stroke and thus favouring early implementation of primary palliative care (PC). Methods A retrospective descriptive study by the analysis of 515 patients who had an acute ischaemic stroke admitted at stroke unit, aged >= 18 years, from January 2017 to December 2018. Previous clinical and functional status data, National Institute of Health Stroke Scale (NIHSS) on admission, and data related to the evolution during hospitalisation were evaluated, relating them to the SFI outcome at discharge and death. The significance level was set at 5%. Results Of 515 patients included, 15% (77) died, 23.3%(120) had an SFI outcome and 9.1% (47) were evaluated by the PC team. It was observed that NIHSS Score >= 16 is responsible for a 15.5-fold increase in the occurrence of death outcome. The presence of atrial fibrillation was responsible for a 3.5-fold increase in the risk of this outcome. Conclusion NIHSS Score is an independent predictor of in-hospital death and SFI outcomes at discharge. Knowledge about the prognosis and risk of developing unfavourable outcomes is important for planning the care of patients affected by a potentially fatal and limiting acute vascular insult.
Keywords: Stroke; Prognosis; Neurological conditions